Microbial Growth Models in Gilthead Sea Bream (Sparus Aurata) Stored in Ice - Carrascosa, Conrado (2016)
"This study analyzes microbiological changes in whole, ungutted farmed gilthead sea bream (Sparus aurata) stored for an 18-day period in ice using traditional methods for mesophilic aerobic bacteria, psychrotrophic, Pseudomonas spp., Aeromonas spp., Shewanella putrefaciens, Enterobacteriaceae, sulphide-reducing Clostridium (Clostridia), and Photobacterium phosphoreum in muscle, skin, and gills, evaluating their seasonal differentiation. Two different statistical models were used to analyze microbiological growth. Simultaneously, physicochemical parameters such as the temperature, pH, biological oxygen demand (BOD5), total dissolved solids, salinity, ammonia nitrogen, and total phosphorus content of growing waters were analyzed. The results showed that by the end of the storage time, specific spoilage bacteria (SSB) such as Pseudomonas spp., Aeromonas spp. and S. putrefaciens as H2S-producing bacteria were dominant in sea bream harvested in temperate water in the Canary Islands. Muscle tissue had least contamination, followed by skin and gills. The values of the analyzed seawater parameters were constant during the four seasons, except that the temperature showed a small difference between winter and summer. Seasonal effects were observed among the fish analyzed, suggesting that the lower levels of contamination detected in winter may have been due to the slight difference observed in water temperature in that season."